EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN PADI SAWAH DI NAGARI TALANG BABUNGO KECAMATAN HILIRAN GUMANTI KABUPATEN SOLOK - Yanti, Desi Hasrilia; Dasrizal, Dasrizal; Zahara, Leni (STKIP PGRI Sumbar, 2013)
Rice harvested in Talang Babungo village Lembah Gumanti District only twice in a year in which the age of the rice grown in the study area with 165 day old rice. This is presumably due to altitude and climatic influences, which Talang Babungo village Lembah Gumanti District a height of 1. 458 meters above sea level. In addition, the topography of the area also varies between the valley and the hilly. This study aims to find studies on Land Suitability Evaluation for Rice Plant in Talang Babungo village Lembah Gumanti District.The method used in this research is descriptive method that gives an idea of the character of the object under study then compared between the objects to each other in order to get a conclusion, how sampling variation by taking a landform units on each level. Sampling was conducted in paddy fields .The results showed that: 1 ) Unit of landforms in the study area consists of volcanic landforms landforms (V) are located in most of Talang Babungo village Lembah Gumanti District, the volcanic plateau landform unit (V1), the slopes of the volcanic foothills and slopes feet volcanic, fluvial landform land of origin, the alluvial plains landform unit (F1), the natural levee (F2) and alluvial terraces (F3), 2) Characteristics of soil texture, soil pH , slope and organic material support to rice crops, while drainage solum and the depth of the soil is a limiting factor for rice crops and 3) rate the suitability of land for rice plantation in Talang Babungo village Lembah Gumanti District categorized into 2 (two) level land suitability, namely According to two (2) units namely land and land units F2.II.Sw.Pb.Pod F1.I.Sw.Tmo.Pod, According enough for 2 (two) units of land and V1.I.Sw.Qou.Pod F3.III.Sw.Tmo.Pod.